F–semigroups - Giraldes, E.; Marques-Smith, P.; Mitsch, H. (Algebra and Discrete Mathematics, 2007)
A semigroup S is called F- semigroup if there exists a group-congruence ρ on S such that every ρ-class contains a greatest element with respect to the natural partial order ≤S of S (see [8]). This generalizes the concept of F-inverse semigroups introduced by V. Wagner [12] and investigated in [7]. Five different characterizations of general F-semigroups S are given: by means of residuals, by special principal anticones, by properties of the set of idempotents, by the maximal elements in (S,≤S) and finally, an axiomatic one using an additional unary operation. Also F-semigroups in special classes are considered; in particular, inflations of semigroups and strong semilattices of monoids are studied.